2017
DOI: 10.1016/j.celrep.2017.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Human Gut-Derived Commensal Bacteria Suppress CNS Inflammatory and Demyelinating Disease

Abstract: SUMMARY The human gut is colonized by a large number of microorganisms (~1013 bacteria) that support various physiologic functions. A perturbation in healthy gut microbiome might leads to the development of inflammatory diseases including multiple sclerosis (MS). Therefore, gut commensals can provide promising therapeutic options for treating autoimmune diseases such as MS. We report identification of human gut–derived commensal bacteria, Prevotella histicola, which can suppress an autoimmune disease in HLA cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
207
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(215 citation statements)
references
References 29 publications
8
207
0
Order By: Relevance
“…Tryptophan‐derived aryl hydrocarbon receptor ligands produced by intestinal commensals can reach the central nervous system (CNS) to modulate astrocyte function and suppress inflammation and neurodegeneration . A recent study showed that the human gut‐derived commensal Prevotella suppresses EAE in a human leukocyte antigen (HLA) class II transgenic mouse model …”
supporting
confidence: 53%
See 1 more Smart Citation
“…Tryptophan‐derived aryl hydrocarbon receptor ligands produced by intestinal commensals can reach the central nervous system (CNS) to modulate astrocyte function and suppress inflammation and neurodegeneration . A recent study showed that the human gut‐derived commensal Prevotella suppresses EAE in a human leukocyte antigen (HLA) class II transgenic mouse model …”
supporting
confidence: 53%
“…9 A recent study showed that the human gut-derived commensal Prevotella suppresses EAE in a human leukocyte antigen (HLA) class II transgenic mouse model. 10 Alterations in the gut microbiome of MS patients has been reported by a number of investigators. We have found increased Methanobrevibacter and decreased Butyricimonas in the gut microbiome of MS patients.…”
mentioning
confidence: 96%
“…Further analysis of commensal bacteria at the family and genus level revealed only minor differences between BACHD and WT mice, where both 3 and 6 month old BACHD mice showed decreased abundance of Prevotella and Bacteroides at the genera level, part of the phylum Bacteroidetes. Consistent with our findings, Prevotella was previously reported to be decreased in the APP/PS1 transgenic mouse model of AD (Shen et al, 2017) and in the experimental autoimmune encephalomyelitis mouse, which recapitulates the main characteristic of MS (Mangalam et al, 2017). Moreover, microbiota profiling in humans also showed decreased Prevotella abundance in MS patients (Chen et al, 2016;Jangi et al, 2016), autistic children (Kang et al, 2013), and PD patients (Keshavarzian et al, 2015;Scheperjans et al, 2015), and was associated with increased gut permeability (Hasegawa et al, 2015).…”
Section: Characterisation Of Microbiota In Bachd and Wt Mice Housed Usupporting
confidence: 90%
“…14 A recent study showed that the human gut-derived commensal Prevotella suppresses EAE in a human leukocyte antigen (HLA) class II transgenic mouse model. 15 We have reported alteration in the gut microbiome of MS patients. 6 Several other groups have also reported dysbiosis in the gut microbiome of MS subjects.…”
Section: Introductionmentioning
confidence: 95%